2012
DOI: 10.1002/chin.201219227
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Microwave Assisted Organic Synthesis: A Green Chemical Approach

Abstract: Review: [265 refs.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Since the first reported microwave utilization techniques in organic synthesis in 1986, microwave techniques have become a recognized laboratory system and they have an important synthetic approach in the field of chemistry [58]. Moreover, these methodologies are therefore being used as an important synthetic tool [59][60][61][62][63]. For these reasons, our group has been interested in using microwave approaches to achieve our synthetic goals [64][65][66][67] in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first reported microwave utilization techniques in organic synthesis in 1986, microwave techniques have become a recognized laboratory system and they have an important synthetic approach in the field of chemistry [58]. Moreover, these methodologies are therefore being used as an important synthetic tool [59][60][61][62][63]. For these reasons, our group has been interested in using microwave approaches to achieve our synthetic goals [64][65][66][67] in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Many surveys have shown that rapid heating and enhancements of chemical yields are achieved with microwaves [12][13][14][15]. In solid chemistry and in heterogeneous solid-liquid systems, many experiments led to significant differences in reaction rates obtained between conventional and microwave heating.…”
Section: About Energy and Heatingmentioning
confidence: 99%
“…During the microwave heating, polar molecules such as water molecules try to orientate with the rapidly changing alternating electric field; thus, heat is generated by the rotation, friction, and collision of molecules (dipolar polarization mechanism). This makes it an ideal choice for heating polar solutions (Ameta et al 2015).…”
Section: Dipolar Polarizationmentioning
confidence: 99%